2000
DOI: 10.1046/j.1365-313x.2000.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐shock tagging: a simple method for expression and isolation of plant genome DNA flanked by T‐DNA insertions

Abstract: SummaryThis paper describes expression pro®les of the Arabidopsis HSP18.2 heat-shock gene promoter by using three different reporter genes, and the application of this promoter to a method we have developed to drive heat-shock-dependent transcription of plant genome DNA¯anked by T-DNA insertions. We show that, irrespective of the location of the T-DNA insertion, an HSP18.2 promoter towards the left border of the T-DNA effectively induces transcription of¯anking genome sequences in response to heat shock. If po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…However, we observed that heat-shock induction was more efficient when applied on in vitro cultured young plantlets, than on mature plants. As previously reported by Matsuhara et al (2000), this suggests that HSP18.2 promoter induction requires a high humidity environment as it is found for in vitro cultures. As pointed out in earlier reviews (Gatz and Lenk, 1998;Padidam, 2003), a good inducible system should have a null or low basal expression.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, we observed that heat-shock induction was more efficient when applied on in vitro cultured young plantlets, than on mature plants. As previously reported by Matsuhara et al (2000), this suggests that HSP18.2 promoter induction requires a high humidity environment as it is found for in vitro cultures. As pointed out in earlier reviews (Gatz and Lenk, 1998;Padidam, 2003), a good inducible system should have a null or low basal expression.…”
Section: Discussionsupporting
confidence: 85%
“…The HSP18.2 promoter presents a weak basal expression at a growth temperature of 23°C, except in vascular bundles and in siliques where a higher expression can be detected. These expression levels are strongly increased by incubation at a temperature of about 37°C (Takahashi et al, 1992;Matsuhara et 18S al, 2000). Despite the basal expression, the heat-inducible gene silencing should be suitable in numerous and various purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Alc gene expression system, which is based on a regulon from Aspergillus nidulans (Felenbok et al 1988;Pateman et al 1983;Sealy-Lewis and Lockington 1984), and the heat-shock inducible promoter (Matsuhara et al 2000;Takahashi et al 1992) were used as inducible promoters. The alcR transcriptional regulator is expressed with the CaMV35S promoter such that, in the presence of ethanol, ALCR induces expression of any gene fused to a modified alcR promoter (Caddick et al 1998).…”
Section: Induction Of Double Flowers In Pharbitis Nil Using a Class-cmentioning
confidence: 99%
“…The alcR transcriptional regulator is expressed with the CaMV35S promoter such that, in the presence of ethanol, ALCR induces expression of any gene fused to a modified alcR promoter (Caddick et al 1998). On the other hand, the heat-shock inducible promoter HSP18.2 from Arabidopsis, encoding a heatshock protein, is indicated to function as a strong inducible system in plants (Takahashi et al 1992;Matsuhara et al 2000). These inducible promoters have been used to construct controllable gene expression systems in plant cells.…”
Section: Induction Of Double Flowers In Pharbitis Nil Using a Class-cmentioning
confidence: 99%